A Proteomic Analysis of Leaf Proteins Expressed in a Brassica Somatic Hybrid and its two Parental Species - Hossain, M.M.; Li, X.; Evans, I.H.; Rahman, M.A. (Plant Tissue Culture and Biotechnology, 2013)
Cabbage (Brassica oleracea L.) is one of the major vegetable crops in the world. Several somatic hybrids between cabbage and Chinese cabbage have been produced. These show hybrid vigor. To identify differences in protein expression that might be relevant to hybrid characteristics of interest, proteins from leaves of a somatic hybrid and its two parents were subjected to 1D and 2D gel analyses, followed by MALDI?TOF and MS/MS of selected spots. 1D gel analysis of the leaf proteins at 14th day post?germination (14 DPG) showed very similar profiles for all three Brassicas. However, upon 2D gel analysis, several differentially expressed protein spots from leaves were discerned. Of the five differentially expressed leaf proteins examined, all the protein spots were photosynthesis? related , including RbcS (the rubisco small subunit). It is possible that differential expression of these photosynthesis?related proteins may relate to the improved growth of the somatic hybrid. Plant Tissue Cult. & Biotech. 23(1): 67?78, 2013 (June) DOI: http://dx.doi.org/10.3329/ptcb.v23i1.15563